Crimean Tatars on the pages of “Musulmanskaya gazeta”: education, charity, culture - Reshat Aliyev (Крымское историческое обозрение)
The article is devoted to the research of important aspects in the social life of the Crimean Muslims in early 20th century: the activities of charitable societies and the spread of education. The author notes the importance of complex research of “Musulmanskaya gazeta” as a historical source. The materials of this newspaper provide an opportunity to shed light on the little-known pages of the history of the Crimean Tatar people.